2012
DOI: 10.1083/jcb.201111077
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of α5β1 integrin ectodomain: Atomic details of the fibronectin receptor

Abstract: The crystal structure of the α5β1 integrin reveals conformational changes and amino acids important for ligand binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
240
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(256 citation statements)
references
References 51 publications
12
240
1
3
Order By: Relevance
“…1C). The LFA-1 βI domain β1-α1 loop, α1-helix, β6-α7 loop, and α7-helix have conformations essentially identical to those in closed β1, β3, β6, and β7 integrin structures (19)(20)(21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…1C). The LFA-1 βI domain β1-α1 loop, α1-helix, β6-α7 loop, and α7-helix have conformations essentially identical to those in closed β1, β3, β6, and β7 integrin structures (19)(20)(21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…The ␤1 integrin heterodimerizes with one of 12 possible ␣ subunits and mediates adhesion, spreading, and migration on multiple ligands, including collagen, laminin, and fibronectin (47,48). A recent study on the crystal structure of ␣5␤1 ectodomain showed that the RGD-binding pocket is surrounded by several N-glycan chains, leaving an exposed surface along the subunit interface (49). Computer modeling also showed that sialylation on an I-like domain may affect the signaling mediated by integrins (44).…”
Section: Discussionmentioning
confidence: 99%
“…Please note the synergy site interactions between the a-subunit (D154) and FN type III repeat 9 (R1379). 48 Fig . 1E shows the C-terminal fibrinogen peptide bound to the open and extended form of aIIbb3.…”
Section: Integrin Conformational Regulation As An Example Of Allostermentioning
confidence: 99%
“…In addition to the influence of ligand-binding and di-valent cations on the conformational equilibrium of micelle embedded integrins, 6 application of tensional forces along the ECM-actin axis induces a catch-bond behavior, 47 thus further stabilizing integrin-ligand interaction and force bearing. Although still incompletely understood, the catch-bond mechanism is likely connected to an approximately 200-fold increase in ligand-binding affinity due to hybrid-domain swing-out, 7 and this open conforma- additional interactions between the synergy site residue R1376 of FN and of D154 of the integrin a-subunit enhance the on-rate of binding 48,49 ( Fig. 1).…”
Section: Integrin Conformational Regulation As An Example Of Allostermentioning
confidence: 99%
See 1 more Smart Citation